Developments and Challenges in Islamic Education Assessment under the GCSE Framework: A Systematic Review - Badrut Tamami; Achmad Maulidi; Siti Maimunah; Kusaeri Kusaeri; Suparto Zakfikam (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Assessment in Islamic Religious Education (PAI) at the secondary level, particularly within the General Certificate of Secondary Education (GCSE) framework, is essential for evaluating students’ mastery of spiritual, cognitive, and affective competencies. This study systematically reviews assessment practices in Islamic education under the GCSE context, drawing on the Systematic Literature Review (SLR) method guided by PRISMA protocols. The review highlights the range of conceptual approaches employed, including argumentation-based assessments, value-oriented frameworks, and the integration of character education. Findings reveal several challenges, such as aligning assessment methods with both national standards and faith-based objectives, ensuring cultural and technological relevance, and addressing limitations in teacher preparedness. At the same time, developments in digital platforms and innovative assessment strategies present opportunities to strengthen validity and inclusivity. The study concludes by offering recommendations for advancing Islamic education assessment in the GCSE framework, particularly through the integration of technology, teacher training, and policy support, thereby contributing to more holistic and contextually grounded evaluation practices.